Digital Etiquette: Educational Strategies - S. N. Pochebut (Дискурс)
Introduction. The modern digital reality imposes its own requirements to the modern paradigm of knowledge acquisition, which with necessity objectivizes the role and importance of social-humanitarian and educational components of the educational process, including through teaching digital etiquette – behavioral culture in practices, networking. The article analyzes the specifics of educational strategies in relation to teaching digital etiquette within school and higher education.Methodology and sources. The paper is based on the application of axiological, interdisciplinary, institutional and systemic approaches to the consideration of digital etiquette learning processes depending on the specifics of each subsystem of the educational process, in particular school and higher education. The research is based on the materials of domestic and foreign sources, scientific publications and websites. In particular, papers of such specialists as D. Stillman, Jo. Stillman, P. Doherty, V. Shi, O. Lukinova, R.I. Mamina and many others are analyzed.Results and discussion. Based on the presented in this article analysis of the specific educational strategies of such institutional structures as school and WSB, the specificity of digital etiquette learning in relation to each of these subsystems of the educational process is analyzed, the main trends of digital etiquette as a digital humanistic knowledge are determined. The main trends include: active attempts to introduce digital etiquette into the educational process, as well as the emergence of new strategies for teaching digital etiquette to generation Z, as the main subject of learning in the modern educational environment within school and higher education.Conclusion. The new realities actualize the role and importance of behavioral culture in the digital space of modern society; first, it concerns the representatives of the young generation – generation Z, which has defined personal freedom as the main value in the practices of their existence. In this regard, the role and importance of the educational component of the modern educational process, an important component of which is the teaching of digital etiquette in the framework of school and HS-education, is increasing. In this case we are talking about different educational strategies in school and HS. In general, regardless of the specifics of educational subsystems and their strategies, teaching digital etiquette is the teaching of digital humanities knowledge, which is a unity of educational and educational, which with necessity reflects the challenges of the new era.